Computer Self-efficacy and Its Relationship with Web Portal Usage: Evidence from the University of the East - Bringula, Rex P.; Sarmiento, Julius Jan M.; Basa, Roselle S. (International Journal of Computing Sciences Research; Vol 1 No 1 (2017), 2017)
Purpose – The University of the East Web Portal is an academic, web-based system that provides educational electronic materials and e-learning services. To fully optimize its usage, it is imperative to determine the factors that relate to its usage. Thus, this study, to determine the computer self-efficacy of the faculty members of the University of the East and its relationship with their web portal usage, was conceived. Method – Using a validated questionnaire, the profile of the respondents, their computer self-efficacy, and web portal usage were gathered. Results – Data showed that the respondents were relatively young ( M = 40 years old), majority had master’s degree (f = 85, 72%), most had been using the web portal for four semesters (f = 60, 51%), and the large part were intermediate web portal users (f = 69, 59%). They were highly skilled in using the computer ( M = 4.29) and skilled in using the Internet ( M = 4.28). E-learning services ( M = 3.29) and online library resources ( M = 3.12) were only used occasionally. Pearson correlation revealed that age was positively correlated with online library resources ( r = 0.267, p < 0.05) and a negative relationship existed between perceived skill level in using the portal and online library resources usage ( r = -0.206, p < 0.05). A 2x2 χ 2 revealed that the highest educational attainment had a significant relationship with online library resources (χ 2 = 5.489, df = 1, p < 0.05). Basic computer ( r = 0.196, p < 0.05) and Internet skills ( r = 0.303, p < 0.05) were significantly and positively related with e-learning services usage but not with online library resources usage. Research Implication – Other individual factors such as attitudes towards the web portal and anxiety towards using the web portal can be investigated.